Is It According to Plan? Evaluating the Effectiveness of the Vocational High School English Programme - Dewi Satria Elmiana; Shiyi Shen (Institut Agama Islam Negeri Palopo, 2022)
Some critics have argued that the quality of the teaching and learning process tends to be inappropriate; that it does not relate to industry needs, current technology, or innovation, and generates inadequate basic skills among students, particularly in learning English (Himpun, 2015; OECD, 2015; Serdyukov,2017). Grounded in the CIPP evaluation model proposed by Daniel L. Stufflebeam, this study evaluates the effectiveness of an aspect of the English study programme that has rarely been examined. The results suggest that the goal achievement of goals in the English programme is significantly affected by teachers’ and students’ activities; by teaching and learning materials; and by the school environment. However, school facilities – one of the pivotal elements - have not significant effect on English programme, even when they are not used properly to support the teaching and learning process. Thus, the implications of this study would be of interest not only to educational practitioners, but also to education policy makers in implementing English- medium education in vocational school.Keywords:CIPP model; English programme; evaluation study; teaching and learning; vocational high school